2018
DOI: 10.1111/asj.13017
|View full text |Cite
|
Sign up to set email alerts
|

New lactic acid bacteria for skin health via oral intake of heat‐killed or live cells

Abstract: Lactic acid bacteria play an essential role in the food industry in the manufacture of many fermented products (cheese, yogurt, fermented vegetables, etc.). Application of these organisms is now being extended to the area of health improvement, as their probiotic activities become known. Probiotics are defined as viable microorganisms that exert a beneficial effect on the health of the host when they are ingested in sufficient quantity. Lactic acid bacteria and bifidobacteria isolated from the human intestine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 63 publications
(102 reference statements)
0
16
0
Order By: Relevance
“…Lactic acid bacteria play an essential role in the food industry in the manufacture of many fermented products, and the application of lactic acid bacteria is now being extended to the area of health improvement. Oral supplementation with lactococcus lactis H61 improves the status of inner forearm and cheek skin in Japanese women by adjusting the balance of intestinal microbes, exerting antioxidant activity, and regulating the immune response [ 14 ].…”
Section: Efficacy and Mechanisms Of Dietary Components In Mitigating Skin Photoaging: Animal And Human Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Lactic acid bacteria play an essential role in the food industry in the manufacture of many fermented products, and the application of lactic acid bacteria is now being extended to the area of health improvement. Oral supplementation with lactococcus lactis H61 improves the status of inner forearm and cheek skin in Japanese women by adjusting the balance of intestinal microbes, exerting antioxidant activity, and regulating the immune response [ 14 ].…”
Section: Efficacy and Mechanisms Of Dietary Components In Mitigating Skin Photoaging: Animal And Human Evidencementioning
confidence: 99%
“…There is increasing animal and clinical evidence that dietary supplementation of functional components can protect skin from photoaging damage. Phytochemicals [ 8 ], functional proteins [ 9 ] and peptides [ 10 ], functional sugars [ 11 , 12 ], functional oils [ 13 ], probiotics [ 14 , 15 ], vitamins [ 16 , 17 ], and minerals [ 18 , 19 ] are well-known to improve the photoaging-associated morphological abnormalities and functional decline.…”
Section: Introductionmentioning
confidence: 99%
“…Lactococcus lactis H61 improved skin status in Japanese women with oral intake of heat-killed or live cells. With regard to live cells in fermented milk made by strain H61, the reported effects are attractive and it is expected that consumption of H61-fermented milk will increase [175]. It is also reported that oral intake of Lactobacillus rhamnosus SP1 improves the appearance of adult acne [176].…”
Section: ( D D D D )mentioning
confidence: 99%
“…Lactococcus lactis H61 improved skin status in Japanese women with oral intake of heatkilled or live cells. With regard to live cells in fermented milk made by strain H61, the reported effects are attractive and it is expected that consumption of H61-fermented milk will increase [183]. It is also reported that oral intake of Lactobacillus rhamnosus SP1 improves the appearance of adult acne [184].…”
Section: Systemic Anti-aging Preparationsmentioning
confidence: 99%